Democratic Governance dan Hak Azasi Manusia: Makna Kebebasan Pers dalam Otonomi Daerah - Ashadi Siregar (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2011)
The transformation of government from centralized toward decentralized system also should be followed by social reforms so that life in public spaces more conducive to the realization of civil society. Building civil society is basically the reverse mainstream policy processes that had been top-down nature of state power to the citizens, transformed in order to create process flows are sharing from the residents as actors who take an active part in public spaces to the policies issued by state power. It’s required the participation of citizens in public life with reference to shared values on the basis of freedom of the press. This paper discusses how the meaning of freedom of the press in the regional autonomy.